1995
DOI: 10.1002/jmr.300080106
|View full text |Cite
|
Sign up to set email alerts
|

An approach towards surface imprinting using the enzyme ribonuclease A

Abstract: An adsorbent showing enhanced selectivity for the enzyme RNase A was prepared by a surface imprinting procedure based on metal coordination. A metal chelating monomer, N-(4-vinyl)-benzyl iminodiacetic acid, was polymerized onto methacrylate-derivatized silica particles in the presence of RNase A and metal ions. Lysozyme and RNase A were separated on the adsorbent used as stationary phase in high-performance liquid chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(122 citation statements)
references
References 23 publications
1
120
1
Order By: Relevance
“…These include the capture of protein complexes at existing surfaces, as in the example shown in Figure 5, 94 and the organisation of surfactant-like molecules in Langmuir monolayers. 123 While these 2-D imprints can show some selectivity, it is unlikely to ever be a suitable method for sensing applications, as non-specific binding is always likely to be high with such materials.…”
Section: Template Presentationmentioning
confidence: 99%
“…These include the capture of protein complexes at existing surfaces, as in the example shown in Figure 5, 94 and the organisation of surfactant-like molecules in Langmuir monolayers. 123 While these 2-D imprints can show some selectivity, it is unlikely to ever be a suitable method for sensing applications, as non-specific binding is always likely to be high with such materials.…”
Section: Template Presentationmentioning
confidence: 99%
“…Using a similar approach, Kempe reported a surface-imprinting procedure for the preparation of selective adsorbents for HPLC separation of proteins (77). They employed a metal chelating monomer, N-(4-vinyl)-benzyl iminodiacetic acid (VBIDA), with methacrylate-derivatized silica particles, in the presence of the protein ribonuclease A (RNase A) and metal ions.…”
Section: Mallik Et Al Used Metal Ions To Coordinate His Residues Viamentioning
confidence: 99%
“…The 3D and 2D protein imprints presented in this review are elegant in design (51,66,77) and have demonstrated fair affinity and specificity. However, several of these protocols are complex and labor-intensive (66), lack generic application (50), and have yet to demonstrate long-term stability.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…This is especially a problem when large template molecules are involved, for example, proteins. Improvements have been made recently, for example, by confining the preparation of imprints to the surface (or interface) of a material [5][6][7] or utilizing materials with a well-defined porosity (e.g., silica) as a solid support for the MIP [8]. In another approach to optimize protein imprinting, Rachkov and Minoura have introduced the concept of epitope imprinting, viz.…”
Section: Key Technologiesmentioning
confidence: 99%